A Rare Case Report of Tropheryma Whipplei-Induced Acute Respiratory Distress Syndrome in an Immunocompetent Patient - Fu Y; Zhou J; He P; Li X (Infection and Drug Resistance)
Yidan Fu,1,* Junfeng Zhou,1,* Ping He,2 Xiaonan Li1 1Department of Critical Care Medicine, the First Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 2Dalian Women and Children Medical Center Group, Dalian, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaonan Li, Email xiaoxiao_sheep@163.comAbstract: Tropheryma whipplei is a rare gram-positive bacterium traditionally associated with Whipple’s disease, primarily presenting with gastrointestinal symptoms. Pulmonary involvement, particularly acute respiratory distress syndrome (ARDS), is extremely rare and poses diagnostic challenges, especially in immunocompetent individuals. We report a rare case of ARDS caused by Tropheryma whipplei in a 28-year-old immunocompetent male with no significant medical history. Traditional diagnostic methods failed to identify the causative pathogen. However, metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid enabled rapid and accurate detection of T. whipplei, allowing timely initiation of targeted antimicrobial therapy with ceftriaxone and trimethoprim-sulfamethoxazole. The patient demonstrated marked clinical improvement and was discharged with no relapse at follow-up. This case highlights the critical diagnostic value of mNGS in atypical ARDS cases and emphasizes the importance of considering T. whipplei in the differential diagnosis, even among immunocompetent individuals.Keywords: Tropheryma whipplei, acute respiratory distress syndrome, whipple’s disease, next-generation sequencing, rare infection